Ganhos de liquidez no sistema bancário após mudanças nos limites de garantias e o possível risco moral - Carvalho, Pedro de Oliveira (2017)
The purpose of this dissertation is to study the role of the Brazilian Deposit InsuranceFund (Fundo Garantidor de Créditos – FGC), evidencing the benefits that an explicit guaranteestructure causes in the banking system. The focus is the last increase in the coverage limit fordepositors, in 2013. In addition, this paper discusses FGC's bailout capacity towards the financial system in order to minimize potential moments of market stress. Next, distortions the guarantee limit ofFGC increase may cause in the financial system will be discussed, highlighting the possibility of moral hazard. This paper also intends to measure the changes in the funding structure of the banking system, highlighting the relative reduction of the risks of refinancing liabilities, the effect of the diversification of funding products and number of investors and the trend of funding costs reduction. It assumes that liquidity have increased and refinancing risk, decreased, leading to funding diversification, with positive effect and declining costs.